Abilities of Mathematical Literacy Based on Self-Confidence in Problem Based Learning with DAPIC Problem-Solving Process - Anwar, Nevi Trianawaty; Budi Waluya, St.; Supriyadi, Supriyadi (Universitas Negeri Semarang, 2018)
This study aimed to 1) explaine the quality of problem-based learning with DAPIC problem-solving process and 2) describe about students' mathematical literacy abilities after being subjected to problem-based learning with DAPIC problem-solving process based on self-confidence. This study used the mixed method with concurrent embedded models. The results of this study indicated that the learning planning obtained quite valid, the implementation of learning with good category, and the average value of mathematical literacy abilities of experimental class students reached the KKM and the proportion of students who complete the KKM reached to 75%. Furthermore, the average mathematical literacy abilities of the experimental class students was better than the control class and the proportion of student’s mastery learning in the experimental class was higher than the control class. Students with low self-confidence still got difficulties in solving problems with the correct resolution steps. Students with self-confidence were already good enough in solving problems based on the correct steps. While students with high self-confidence were very good in solving the given questions so that the steps were quite complete and correct.